O jornalismo independente na cobertura da desinformação da extrema direita no Youtube: análise do The Intercept Brasil - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The work addresses independent journalism in journalistic production about far-right disinformation on the YouTube platform. The research problem seeks to uncover: What characteristics and elements make up The Intercept Brasil's coverage of disinformation on YouTube? The study is justified by the narrative covered by the independent news agency, TIB, about the use of YouTube as a tool for antidemocratic speeches and disinformation. The methodology adopted in the investigation consists of conducting an interview with a journalist from The Intercept Brasil and analyzing the report “Youtube makes right-wing channels make money by spreading lies about coronavirus”, published on March 25, 2020. Regarding the results, it highlights questions that arise about the financing of content producers on the internet. What is observed is that there are people who do this for profit, but there are also people producing disinformation content for ideological reasons.
Keywords: Jornalismo; Democracia; The Intercept Brasil; Youtube (Recurso eletrônico); Desinformação; Extremistas de direita; Journalism; Democracy; CNPQ::CIENCIAS SOCIAIS APLICADAS